Improving Communication Skills and Mathematical Disposition by Inquiry Model Alberta Method - Supiyanto, Supiyanto; Hendriana, Heris; Maya, Rippi (PRISMA, 2020)
ABSTRACTThis study aims to improve communication skills and mathematical disposition in mathematical learning using inquiry method of alberta model and assosiation between the two. The The subjects of this study are students of SMP class VII as many as two classes with a total of 64 students. The instrument used in data collection is a written test for communication and mathematical disposition. The research method used in this research is using quasi experiment. Communication data and mathematical dispositions were analyzed using Mann Whitney nonparametric tests. The results obtained from this study were obtained: (1) Improvement of students' communication skills whose learning method using Inquiry Model Alberta is better than the usual method; (2) The mathematical disposition of students whose learning method using the Inquiry Model Alberta is better than the usual method; (3) There is a assosiation between communication ability with mathematical disposition of students whose learning method using Inquiry Model AlbertaKeywords: Communication, Mathematical Disposition, Alberta Model Inquiry Method.Â